Metagenomic detection of protozoan parasites on leafy greens aided by a rapid and efficient DNA extraction protocol - Naushad, Sohail; Gao, Ruimin; Duceppe, Marc-Olivier; Dupras, Andree Ann; Reiling, Sarah J.; Merks, Harriet; Dixon, Brent; Ogunremi, Dele (Frontiers in Microbiology, 2025)
IntroductionInfections with protozoan parasites associated with the consumption of fresh produce is an on-going issue in developed countries but mitigating the risk is hampered by the lack of adequate methods for their detection and identification.Materials and methodsWe developed a metagenomic next-generation sequencing (mNGS) assay using a MinION sequencer for the identification of parasites in intentionally contaminated lettuce to achieve a more accurate and rapid method than the traditional molecular and microscopy methods commonly used for regulatory purposes. Lettuce (25 g) was spiked with varying numbers of Cryptosporidium parvum oocysts, and microbes washed from the surface of the lettuce were lysed using the OmniLyse device. DNA was then extracted by acetate precipitation, followed by whole genome amplification. The amplified DNA was sequenced by nanopore technology and validated with the Ion Gene Studio S5, and the generated fastq files raw reads were uploaded to the CosmosID webserver for the bioinformatic identification of microbes in the metagenome. To demonstrate the ability of the procedure to distinguish other common food and waterborne protozoan parasites, lettuce was also spiked with C. hominis, C. muris, Giardia duodenalis and Toxoplasma gondii individually or together.ResultsThe efficient lysis of oocysts and cysts was a prerequisite for the sensitive detection of parasite DNA and was rapidly achieved within 3 min. Amplification of extracted DNA led to the generation of 0.16–8.25 μg of DNA (median = 4.10 μg), sufficient to perform mNGS. Nanopore sequencing followed by bioinformatic analysis led to the consistent identification of as few as 100 oocysts of C. parvum in 25 g of fresh lettuce. Similar results were obtained using the Ion S5 sequencing platform. The assay proved useful for the simultaneous detection of C. parvum, C. hominis, C. muris, G. duodenalis and T. gondii.DiscussionOur metagenomic procedure led to the identification of C. parvum present on lettuce at low numbers and successfully identified and differentiated other protozoa either of the same genus or of different genera. This novel mNGS assay has the potential for application as a single universal test for the detection of foodborne parasites, and the subtyping of parasites for foodborne outbreak investigations and surveillance studies.